The Correlation of Education and Income Toward Community Behaviors in Disposing Waste to Sago River of Pekanbaru - ., Suryani (KnE Life Sciences, 2019)
Sanitary Office of Pekanbaru recorded the waste produced by around 1.3 million residents of Pekanbaru is 500 tons / day or 2.6 kilograms per recident everyday. During 2016, recorded flooding incidents in Pekanbaru and around Riau Province occurred because of the damage of river boundary. The main Sources of water pollution was domestic and household wastes. The human behavior was the biggest cause of environmental damage. The aim of this research was for finding out the correlation of education and income toward community behaviors in disposing household waste to sago river. This research included into quantitative type with crossectional approach. Independent variable of the research was education and income. The population was all of housewives living around sago river about 974 people. The sample was about 284 people who selected by Stratified Random Sampling technique. The instrumen used was questionnaire and observation sheet. The primary data was from questionnaire and abservation sheet, while secondary data was taken from Sukaramai Village Office of Pekanbaru. The data was analyzed by chi square test with